Development of Islamic Economic Concepts in Mohammad Hatta's Thoughts on People's Economy: An Analytical Study of Cooperatives and Society - Malahayatie; Ramadhana, Safna; Rizki, Munawar (Journal of Islamic Economic and Business Research, 2025)
This study analyzes the development of Islamic economic principles within Mohammad Hatta’s concept of the people’s economy, with a focus on the cooperative system as a foundational instrument for achieving economic justice and social welfare. Using a qualitative library research methodology, the analysis focuses on Hatta’s major economic works, which discuss the structure, objectives, and ethical foundations of cooperatives in relation to Islamic economic values. The purpose of this study is to explore how Hatta conceptualizes the people’s economy and to examine the extent to which his ideas align with and contribute to the development of Islamic economic thought. The findings reveal that Hatta’s model of the people’s economy emphasizes collective ownership, social solidarity, self-help, and economic democracy through production, credit, and consumption cooperatives, all of which reflect principles of fairness, mutual assistance, and moral responsibility. The study further finds that the values embedded in Hatta’s economic vision are consistent with Islamic principles such as Tawhid, Mashlahah, justice, cooperation, and voluntary consent in transactions. However, certain cooperative practices, particularly in consumption and credit structures, require reform to eliminate debt-based mechanisms and penalties that conflict with sharia provisions on leniency and prohibitions against exploitation. This study concludes that Hatta’s people’s economy presents a strong philosophical and practical foundation for the advancement of Islamic economics, offering a model that integrates ethical values with social empowerment and economic inclusivity.